1985
DOI: 10.1002/jcp.1041250223
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine uptake, transport, and metabolism in human erythrocytes

Abstract: Using rapid kinetic techniques, we have determined the kinetics of zero-trans influx and equilibrium exchange of adenosine, and its uptake and in situ phosphorylation at 25 degrees C in human erythrocytes which were pretreated with 2'-deoxycoformycin to inhibit deamination of adenosine. Both the Km and Vmax for adenosine transport were about 300 times higher than those for the in situ phosphorylation of adenosine (Km about 0.2 microM), so that the first order rate constants for both processes were about the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 37 publications
5
34
1
Order By: Relevance
“…In hyperhomocysteinemia, erythrocytes are relevant in the regulation of circulating endogenous adenosine because adenosine is efficiently taken up by erythrocytes through the dipyridamole-sensitive transporter and because homocysteine and AdoHcy are increased in erythrocytes of patients with hyperhomocysteinemia. [11][12][13] Freshly isolated erythrocytes were resuspended in MOPS buffer to obtain a 2% solution. Fifty-L portions were incubated at 37°C with L-homocysteine (100 mol/L) in DTT and with DTT alone for 10 minutes (paired experiments).…”
Section: Adenosine Uptake In Isolated Erythrocytesmentioning
confidence: 99%
“…In hyperhomocysteinemia, erythrocytes are relevant in the regulation of circulating endogenous adenosine because adenosine is efficiently taken up by erythrocytes through the dipyridamole-sensitive transporter and because homocysteine and AdoHcy are increased in erythrocytes of patients with hyperhomocysteinemia. [11][12][13] Freshly isolated erythrocytes were resuspended in MOPS buffer to obtain a 2% solution. Fifty-L portions were incubated at 37°C with L-homocysteine (100 mol/L) in DTT and with DTT alone for 10 minutes (paired experiments).…”
Section: Adenosine Uptake In Isolated Erythrocytesmentioning
confidence: 99%
“…21 In addition, the plasma half-life of adenosine is short (seconds-minutes), 25 due in large part to its rapid degradation by adenosine deaminase contained within red blood cells. 26 Thus, while a possible synergistic contribution cannot be excluded, 27 these two factors essentially preclude the blood-borne transport of this nucleotide in appreciable quantities from a remote, ischemic ''trigger'' organ [7][8][9][10][11][12] to the heart. If adenosine is not the primary humoral trigger for preconditioning at a distance, what are the other possibilities?…”
Section: Identity Of the Protective Humoral Trigger?mentioning
confidence: 99%
“…In our earlier study, we showed that LY2033298 also displayed positive cooperativity with ACh in binding affinity (16-fold) indicating that there is no efficacy modulation by LY2033298 with the parent agonist (Valant et al, 2012). Similarly to ACh, adenosine is also rapidly metabolized (by adenosine deaminase) to inosine (Plagemann et al, 1985) ( Supplemental Fig. 1B); inosine displayed greater than 1000-fold lower potency at the A 1 -AR in ERK1/2 phosphorylation compared with its parent ligand, adenosine.…”
mentioning
confidence: 93%